Public Participation in Regulatory Design: A Public Service Perspective - Rahmanto, Tony Yuri (Jurnal Ilmu Pemerintahan : Kajian Ilmu Pemerintahan dan Politik Daerah, 2025)
Regulations concerning DKI Jakarta Province no longer designate the area as the nation's capital. Issues arise when the formulation of regulations appears to lack optimal community engagement, suggesting the potential for regulations that benefit specific parties or groups. This study employs a qualitative methodology, specifically a literature review, which entails the aggregation of materials and data from various sources, including books, journals, and websites pertinent to the article's theme. The study's results demonstrate the essential and strategically important role of community involvement in the development of laws and regulations. This occurs because regulations and policies are formulated with the community's interests and objectives in consideration when they are actively engaged. Increased legislation and regulations favoring public interests will be enacted due to the recognition of the significance of public participation. Integrating the community into significant meetings related to law formation, including work meetings, committee sessions, drafting team discussions, and plenary assemblies as decision-making forums, is an effective method to guarantee public involvement in the legislative process. Public hearings, consultations, and additional avenues are equally significant. Moreover, to effectively align individuals' aspirations with legal standards, council members must authentically embody the ethos of public service. The public must be discerning and judicious in their choice of representatives who truly embody this spirit. Nonetheless, the populace ought to possess the greatest access to governmental procedures to facilitate their involvement in the formulation of laws and regulations. The public should have convenient access to this information and be able to obtain clear details through various offline and online sources.